Estimated annual healthcare costs after acute pulmonary embolism: results from a prospective multicentre cohort study - Mohr, Katharina; Mildenberger, Philipp; Neusius, Thomas; Christodoulou, Konstantinos C; Farmakis, Ioannis T; Kaier, Klaus; Barco, Stefano; Klok, Frederikus A; Hobohm, Lukas; Keller, Karsten; Becker, Dorothea; Abele, Christina; et al. (European heart journal - quality of care and clinical outcomes, 2024)
Patients surviving acute pulmonary embolism (PE) necessitate long-term treatment and follow-up. We estimated, the chronic economic impact of PE on the German healthcare system.We calculated the direct cost of illness during the first year after discharge for the index PE, analysing data from a multicentre prospective cohort study in Germany. Main and accompanying readmission diagnoses were used to calculate DRG-based hospital reimbursements; anticoagulation costs were estimated from the exact treatment duration and each drug's unique national identifier; and outpatient post-PE care costs from guidelines-recommended algorithms and national reimbursement catalogues. Of 1017 patients enrolled at 17 centres, 958 (94%) completed ≥3-month follow-up; of those, 24% were rehospitalized (0.34 [95% CI 0.30-0.39] readmissions per PE survivor). Age, coronary artery, pulmonary and kidney disease, diabetes, and (in the sensitivity analysis of 837 patients with complete 12-month follow-up) cancer, but not recurrent PE, were independent cost predictors by hurdle gamma regression accounting for zero readmissions. The estimated rehospitalization cost was €1138 (95% CI 896-1420) per patient. Anticoagulation duration was 329 (IQR 142-365) days, with estimated average per-patient costs of €1050 (median 972; IQR 458-1197); costs of scheduled ambulatory follow-up visits amounted to €181. Total estimated direct per-patient costs during the first year after PE ranged from €2369 (primary analysis) to €2542 (sensitivity analysis).By estimating per-patient costs and identifying cost drivers of post-PE care, our study may inform decisions concerning implementation and reimbursement of follow-up programmes aiming at improved cardiovascular prevention.
Online veröffentlicht ahead of print: 1. Juli 2024, Korrektur und Schriftsatz: 11. Juli 2024
Gesehen am 10.02.2025